EFEKTIVITAS PELAKSANAAN PARENTING EDUCATION DI PAUD TARAM SKB KABUPATEN TRENGGALEK - DEDY SUKRISNO (Jurusan Pendidikan Luar Sekolah Fakultas Ilmu Pendidikan UNESA, 2013)
Parenting Education is a synergistic activity between EARLY CHILDHOOD educators and the parents through education program for parents. This study uses qualitative approach in order to understand the phenomenon of what is experienced by the subject of research in a descriptive way, in the form of words and language. The methods used in this study are the method of observation, interview and documentation. The result of data analysis demonstrated that the effectiveness of implementation in parenting education of early childhood at Taram SKB – Trenggalek runs well, in accordance with technical guidance issued by the Director General PAUDNI as research guidelines and suited the theory. The effectiveness of implementation in parenting education of early childhood at Taram SKB – Trenggalek can be known from learning components such as: andragogy approach used in parent’s learning, materials, methods, media, atmosphere and setting of learning that are well synergic so that the desired output by institutions that parents understand parenting education materials, can apply it to their children. There are some obstacles in the implementation, so the advice that is given by researcher, is: that early childhood educators more excited again to strive for the parents more active when the learning takes place and presenters using LCD which is owned by SKB Trenggalek, so parenting education that is in progress can be more interesting. Keywords: effectiveness, and parenting education Abstrak Dalam upaya mengembangkan kemampuan dan potensi anak usia dini diperlukan suatu program yang dapat membantu dan mendukung terhadap perkembangan anak, yang salah satunya adalah diadakannya kegiatan yang mensinergikan antara pendidik PAUD dengan orang tua melalui program pendidikan orang tua (parenting education). Penelitian ini bertujuan untuk mengetahui Efektivitas Pelaksanaan Parenting Education Di Paud Taram SKB Kabupaten Trenggalek. Sasarannya adalah para orangtua yang menjadi peserta didik di lembaga PAUD. Metode yang digunakan dalam penelitian ini adalah metode observasi, wawancara dan dokumentasi. penelitin ini mengunakan penelitian kualitatif. Hasil penelitin menunjukkan bahawa Efektivitas Pelaksanaan Parenting Education Di Paud Taram SKB Kabupaten Trenggalek dapat berjalan dengan baik, itu dapatdilihat dari bentuk-bentuk kegiatan yang sudah sesuai dengan petunjuk teknis yang diterbitkan oleh DIRJEN PAUDNI, meskipun ada beberapa kendala dari pelaksanaannya. Tetapi pendidik PAUD sekaligus pemateri Parenting Education dapat mengatasinya dengan berbagai cara. Sedangkan untuk materi yang diberikan pada orangtua sesuai dengan kebutuhan orangtua dalam mengasuh dan mendidik anaknya. Kata kunci: efektivita,s dan parenting education